The use of pesticides and its association with parkinson's disease - Rodrigues, Maria Lúcia Ferreira; Murata, Marília Pinto Ferreira (Seven Editora, 2023)
Brazil is one of the countries that consumes the most pesticides, and as a consequence, both rural workers and society in general are exposed to the risks that this use poses to physical and mental health. In this sense, Parkinson's disease exemplifies such risks, as it is a neuronal disorder that presents motor and non-motor symptoms that affect quality of life. The main objective of the research was to observe the relationship between the development of Parkinson's disease and the use of pesticides, considering that it is a neurodegenerative disease that affects rural workers who handle products with such active ingredients, as well as the general population that consumes crops treated with them. Therefore, the characteristics that permeate the disease were described, and data from Brazilian regions and states were collected, with a focus on Paraná regarding the use of associated active ingredients (Paraquat, Mancozeb, and Glyphosate), the crops that use them, and also Parkinson's mortality rates by region and states from 2013 to 2020, in order to establish a parallel between use and mortality. It was observed that both mortality and pesticide use increased during the associated period. The Central-West, South, and Southeast regions were the ones that used the three analyzed active ingredients the most, while the Northeast, Southeast, and South had the highest mortality rates. Additionally, parallels between use and mortality were observed in certain states, such as Rio Grande do Sul, for example. In conclusion, Parkinson's disease is multifactorial and may be associated with pesticides containing the active ingredients Glyphosate, Mancozeb, and Paraquat. In Brazil, Parkinson's mortality is increasing, as well as the use of these products, which, with the exception of Paraquat, which has been legally banned, rank among the top 10 most widely used pesticides. This calls for continuous studies that analyze the propensity for disease development and the use of these active ingredients. DOI:https://doi.org/10.56238/globalhealthprespesc-051